PENERAPAN ASESMEN SUMATIF PADA MATA PELAJARAN IPAS DALAM KURIKULUM MERDEKA DI SDS TARBIYATUL ISLAM SAMBAS - Rona Rona (Adisam Publisher, 2026)
The implementation of summative assessment is to measure whether predetermined learning objectives have been achieved. This summative assessment is carried out at the end of the semester to determine whether or not the student passes. However, the implementation of summative assessment at Tarbiyatul Islam Sambas Elementary School is very much contrary to the Merdeka curriculum assessment criteria, where the semester final assessment criteria in the Merdeka curriculum are that no students are held back, even if their private and public examination scores do not meet the criteria. This summative assessment is carried out using test techniques. The test technique used is a series of questions in the form of multiple choice and essay questions. This study aims to analyse the application of summative assessment used in IPAS learning at SDS Tarbiyatul Islam Sambas. The research method used is qualitative descriptive research. Descriptive data collection was obtained from observation, interview and documentation. The subjects in this study were IPAS teachers at SDS Tarbiyatul Islam Sambas as research subjects and documentation as support. The data collection techniques were observation, interviews, and documentation. To find out the research results, it is necessary to describe the results of the interview research on IPAS teachers at SDS Tarbiyatul Islam Sambas in summative assessment in IPAS learning. The results of the research on the application of summative assessment in IPAS learning at SDS Tarbiyatul Islam are quite effective.